Analisis Kepuasan Penerapan Sistem Informasi Perpustakaan Universitas Yppi Rembang Menggunakan Pieces Framework (Jurnal Ilmiah Sistem Informasi dan Teknik Informatika (JISTI), 2024)
One of the parts of information that is so rapidly evolving is the information system. Every system has its advantages and weaknesses, and in order for the system to work well and efficiently, they need to be modified. To this, an analysis of the level of efficiency and effectiveness of the system is needed. The PIECES Framework, which consists of six indicators related to performance, information, economics, control/security, efficiency, and service, is one of the methods that can be used to analyze systems. Many studies have been conducted on the evaluation of the system, but few have been done to evaluate the Library Information System owned by the UYR. The aim of this study is to determine the level of user satisfaction with the library information system as well as to identify the advantages and disadvantages of such a system. The research uses a quantitative descriptive approach, and data is collected through observations and questionnaires. The data analysis was done using interval scales and mean formulas. The results of the study showed that of the six domains of the PIECES framework methodology said well with mean mean values namely performance (4.69), information (4.66), economics (4.16), control/security (4.47), efficiency (4.7), service. (4.6). According to the research carried out, the information system of the YPPI University Library Rembang can be used well according to PIECES analysis, and is quite effective and efficient to use.